Serum uric acid level between normotensive and pre-eclamptic patients in third trimester of pregnancy and perinatal outcome (Northern International Medical College Journal, 2020)
Background : Preeclampsia is associated with maternal and neonatal complications. It has been indicated that increased uric acid might have a predictive role on preeclampsia. Several studies have demonstrated a relation between elevated maternal serum uric acid levels and adverse maternal and fetal outcome. The aim of this study was to find out the association of serum uric acid level between normotensive and pre-eclamptic (PE) patients in third trimester of pregnancy and perinatal outcome.Methodology : A case control study was conducted in the department of the Obstetrics and Gynaecology in Dhaka Medical College Hospital from July 2017 to June 2018. A total number of 100 pregnant women in third trimester of pregnancy attending in Obstetrics and Gynaecology department of Dhaka Medical College Hospital were selected purposively as study subjects. Among them 50 diagnosed cases of preeclampsia were selected as cases with age range of 18-35 years and 50 normal healthy age matched pregnant women as controls. Pregnant women with pre-existing hypertension, diabetes mellitus and renal disease were excluded from the study by history, clinical examination and relevant laboratory investigations.Results : The mean serum uric acid level was found 4.49±1.72 mg/dl in normotensive group and 7.03±1.89 mg/dl in preeclampsia group. Serum uric acid was significantly higher (p